Effect of desiccation on the ultrastructural appearances of Acinetobacter baumannii and Acinetobacter lwoffii. Issue 10 (October 1998) - Houang, E T; Sormunen, R T; Lai, L; Chan, C Y; Leong, A S
Abstract : An Acinetobacter baumannii isolate survived desiccation beyond 30 days and an Acinetobacter lwoffii isolate up to 21 days. For both species, desiccation resulted in a significant increase in the proportion of round cells (A baumannii, 40% to 80%; A lwoffii, 51% to 63%) and a significant decrease in rod shaped cells (A baumannii, 58% to 13%; A lwoffii, 46% to 34%). Electronmicroscopic examination showed that there was also a corresponding significant increase in the cell wall thickness (A baumannii, up to 53%; A lwoffii, up to 26%). Desiccated A baumannii cells became more electron-dense and had significantly thicker cell walls (x1.3) than those of A lwoffii. Cell wall structures of A baumannii strains with different abilities to resist desiccation deserve further study.